2000
DOI: 10.1787/524744315352
|View full text |Cite
|
Sign up to set email alerts
|

EMU, The Euro and The European Policy Mix

Abstract: One year ago most economic observers predicted that "fundamentals" were such that the euro was set to appreciate. In the event, the opposite has occurred. This has rekindled a debate on how well foreign exchange markets reflect fundamental determinants and led to calls for greater exchange rate stability, possibly through the introduction of formal exchange rate target zones. The first part of the paper focuses on these issues. It also looks at the euro’s prospects as an international currency. To give a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…We have studied theoretically a rodlike polymer immersed in a nematic environment and described the effect of a nematic solvent on small fluctuations of the tangent vector perpendicular to the rod axis. We were thus able to calculate the physically interesting properties associated with our combined polymer and nematic system, including tangent−tangent correlation functions, and the scattering structure factor, which reproduces qualitatively known experimental results well. …”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We have studied theoretically a rodlike polymer immersed in a nematic environment and described the effect of a nematic solvent on small fluctuations of the tangent vector perpendicular to the rod axis. We were thus able to calculate the physically interesting properties associated with our combined polymer and nematic system, including tangent−tangent correlation functions, and the scattering structure factor, which reproduces qualitatively known experimental results well. …”
Section: Discussionsupporting
confidence: 58%
“…Shown in Figures −4 are plots of S ( Q z , Q ⊥ ) (where Q z = q z L and Q ⊥ = q ⊥ L ) for three different values of the Frank elasticity constant, with all other constant parameters held fixed. We can see from Figures −4 the characteristic “bow-tie” scattering pattern as typically found for nematic rods. We can also see from Figures −4 that as the Frank constant increases (i.e., the solvent/environment becomes more nematic), the associated polymer rod scattering becomes less intense along the Q z axis. This is consistent with the physical picture that as the nematic order increases, the polymer rod becomes more and more aligned along the nematic director.
2 Isointensity contour plot of S ( Q z , Q ⊥ ) vs ( Q ⊥ , Q z ) with κ t / L = 10 -1 , L / r = 10 2 , Γ L = 10 4 , and a value of the Frank elasticity constant given by κ n L = 3 × 10 -3 .
3 Isointensity contour plot of S ( Q z , Q ⊥ ) vs ( Q ⊥ , Q z ) with κ t / L = 10 -1 , L / r = 10 2 , Γ L = 10 4 , and a value of the Frank elasticity constant given by κ n L = 3 × 10 -1 .
4 Isointensity contour plot of S ( Q z , Q ⊥ ) vs ( Q ⊥ , Q z ) with κ t / L = 10 -1 , L / r = 10 2 , Γ L = 10 4 , and a value of the Frank elasticity constant given by κ n L = 3 × 10 1 .
…”
Section: Scatteringmentioning
confidence: 65%
See 1 more Smart Citation
“…The scattered intensity I ( q ) ∝ P ( q ) S ( q ), where P ( q ) is the aggregate form factor and S ( q ) is the structure factor of the solution. The organization of the aggregates in a plane normal to the nematic director can be described, to a good approximation, by the structure factor S 2D ( q ) of a two-dimensional liquid, , which to first order is described by a two-dimensional hard disk fluid as follows: G = 1/(1 − η) 3/2 , χ = (1 + η)/(1 − η) 3 , A = [1 + (2η − 1)χ + 2η G ]/η, B = [(1 − η)χ − 1 − 3η G ]/η. η is the packing fraction of the disks, R is the disk radius, and J 0 and J 1 are the zeroth and first-order Bessel functions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They are 1 nm thick, about 25 nm wide, and several microns long. Previous light scattering measurements have shown that the largest measured dimension in solution, most likely the persistence length, is about 300−500 nm. In fact, some bending of the ribbons, apparently more difficult in the plane of the ribbons than out of it, is visible by transmission electron microscopy . While concentrated samples, between 8.6 and 0.4 mol/L vanadium concentration (i.e., between 10 and 250 H 2 O moles per V 2 O 5 mole), are gels, a sol is obtained by adding more water.…”
Section: Introductionmentioning
confidence: 99%